PEMBAGIAN HARTA BERSAMA SETELAH PERCERAIAN DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU (Studi Kasus Terhadap Putusan Pengadilan Agama Rengat Nomor : 062/Pdt.G/2009/PA Rengat) - Fendra Yuli Hardiyanto; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Joint property is marital property acquired during marriage by both husband and wife, who are in the power of the husband and wife together, so that use should be made with the consent of both parties (unless provided otherwise in the marriage covenant). Joint property is set in the Compilation of Islamic Law Article 97 which states: "widow or widower who divorced each entitled to half of the joint property to the extent not otherwise stipulated in the marriage covenant". One of the underlying case verdict of joint property with Article 97 Compilation of Islamic Law is Case Number:062/Pdt.G/2009/PA. The principal issues in this research, namely: How does the setting on the Division of joint property after Divorce according Compilation of Islamic Law? and How consideration of the judges on the basis of the division of joint property after divorce in Decision Case Number: 062 / Pdt.G/2009/PA.RGT? This research views of the kind, the data used, and based on the core issues in this research, including normative legal research or legal research literature, the research done by using secondary data in the form of a copy of the decision on Case Number: 062 / Pdt.G / 2009 / PA .RGT as the main data research and other secondary data. This is a descriptive research that illustrates clearly and in detail about the legal reasoning of judges and application of the rules of joint property in Case Number: 062 / Pdt.G / 2009 / PA.RGT. In this case of the partnership has been happening since the beginning of the marriage both parties. The case of all the property of the partnership between the defendant and the plaintiff's entire property. Because of this partnership is not limited in accordance with the discussion shirkah mufawadhah. Partnerships have property that can be used by a husband and wife to finance their daily lives and their children. The husband and wife as a whole with their children. Judge basic considerations in deciding civil cases Number: 062 / PDT.G / 2009 / PA.RGT not meet the principle of legal certainty, because in this case the judges accept the testimony of plaintiff's brother. In evidence presented to the witness if the witness testified the knowledge of a property, then the witness should not have blood ties with one of the litigants, which is related by blood, by marriage or family member of one of the parties in a straight descent in accordance with Article 145 Paragraph 1e (a) HIR and Article 172 Paragraph 1 Rbg.Keywords: community property – divorce – Rengat